HUBUNGAN ANTARA BERBAGAI FAKTOR RESIKO TERHADAP KEJADIAN KARSINOMA SEL SKUAMOSA SERVIKS DI RSPAD GATOT SOEBROTO BULAN OKTOBER - DESEMBER TAHUN 2018 - Pratiwi Agustianti, (2021)
Cervical cancer is a malignancy in cervical tissue and is the second leading incidence of malignancy in Indonesian. The incidence of malignancy in the cervix is the most common type of squamous cell carcinoma (SCC) reaching 80%, indicating that squamous cell carcinoma can have mortality and morbidity for cases of all ages. This study aims to determine the relation between risk factors (age at first sexual intercourse, total parity, use of hormonal contraceptives, duration of hormonal contraception, and smoking) to the incidence of cervical squamous cell carcinoma. This research is an analytical study with cross sectional design to 50 patients who came to poly obgyn Gatot Soebroto Hospital in period of October until December 2018. Data obtained by interviewing, filling out questionnaires and analyzed by univariate, bivariate and multivariate analysis. The Chi Square test shows that there are four factors that significantly determine the incidence of SCC; age first sexual intercourse 4.6 times incrase risk, parity ≥ 3 will incrase 6.4 times for SCC insidence, use of hormonal contraceptives is 4.1 times incrase risk, duration use of hormonal contraceptives ≥ 4 years will be 0.2 times more risky SCC. The results of the Multiple logistic regression in this riset showed that 2 variables, parity> 3 and duration of time using contraception hormonal had the most influence on the causes of cervical squamous cell carcinoma.